«Արարատ» ամսագրի հրատարակումը վերսկսելու Մայր Աթոռ Սուրբ Էջմիածնի ջանքերը 1920-ական թուականներին - Սուքիասեան, Համօ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В декабре 1920 года после советизации Армении культурные и образовательные учреждения Первопрестольного Святого Эчмиадзина, в том числе типография, подверглись экспроприации. Это обстоятельство осложнило издание не поощряемой властями церковно-религиозной литературы. В таких неблагоприятных условиях Святой Эчмиадзин приложил усилия для возобновления издания журнала «Арарат», прекратившего издаваться в 1919 году. Получив разрешение от советских властей, с октября 1923 года начались работы по изданию церковно-религиозной периодики. Несмотря на разрешение, серьезнейшим препятствием для издания периодики была нехватка финансовых средств․ In December 1920, after the Sovietization of Armenia, the cultural and educational institutions of the Mother See of Holy Etchmiadzin, including the printing house, were expropriated. This circumstance complicated the publication of religious-ecclesiastical literature not encouraged by the authorities. In such unfavorable conditions, the Mother See made efforts to resume the publication of “Ararat” monthly ceased to be published in 1919. With permission of the authorities of Soviet Armenia, in October 1923, the Mother See of Holy Etchmiadzin started works on the publication of religious-ecclesiastical periodicals. Despite the resolution, a serious obstacle to the publication of periodicals was the lack of financial resources.
Keywords: Religion; Armenian church